The monetary transmission mechanism in the euro area : has it changed with the EMU? A VAR approach, with fiscal policy and financial stress considerations - Afonso, António (2014)
We study whether the adoption of the Euro and a single monetary policy have brought about a change in the monetary transmission mechanism and between the interactions of monetary policy, fiscal policy and financial stress in the Euro area. We find that the stylized facts of monetary transmission remain valid, but the response of output and, especially, fiscal and financial stress variables to a monetary policy shock, seems to be stronger in the post-EMU period. Regarding fiscal and financial stress shocks, the inclusion in the post-EMU period of subprime and sovereign debt crises yields, changes, not only in the scale, but also in the patterns of the responses of our model’s main variables.